Partisipasi Masyarakat Desa Jagara dalam Pengembangan Objek Wisata Waduk Darma Kabupaten Kuningan - Virgi Fathurrahman; Ina Helena Agustina; Riswandha Risang Aji (UPT Publikasi Ilmiah Unisba, 2024)
Abstract. Darma Reservoir is a leading tourist destination in Kuningan Regency. However, the development of this tourist attraction has not been maximized because the local community is less involved, resulting in the potential of nature and society is not optimal and has decreased. Factors causing the decline in tourism visits include the low human resources of tourism managers, the lack of formation of tourism communities, the lack of coordination between the government and the community, the lack of promotion, and the management of tourism potential that has not been optimized. This study aims to identify the level of participation of the Jagara Village community in the development of the Darma Reservoir tourist attraction. Using a qualitative approach, this research analyzes the results of observations and interviews with a qualitative descriptive analysis method, which transforms raw data into data that is easy to understand and interpret. The sampling technique used was purposive sampling. The results of the analysis show that the participation of the Jagara Village community in the development of the Darma Reservoir is only visible at the implementation stage as business actors and supporters of activities. However, in the planning and supervision stages, their participation is still minimal and even not involved. Abstrak. Waduk Darma adalah destinasi wisata unggulan di Kabupaten Kuningan. Namun, pengembangan objek wisata ini belum maksimal karena masyarakat lokal kurang terlibat, mengakibatkan potensi alam dan masyarakat tidak optimal dan mengalami penurunan. Faktor penyebab penurunan kunjungan wisata meliputi rendahnya sumber daya manusia pengelola wisata, belum terbentuknya komunitas wisata, kurangnya koordinasi antara pemerintah dan masyarakat, kurangnya promosi, serta pengelolaan potensi wisata yang belum optimal. Penelitian ini bertujuan untuk mengidentifikasi tingkat partisipasi masyarakat Desa Jagara dalam pengembangan objek wisata Waduk Darma. Menggunakan pendekatan kualitatif, penelitian ini menganalisis hasil observasi dan wawancara dengan metode analisis deskriptif kualitatif, yang mentransformasikan data mentah menjadi data yang mudah dimengerti dan diinterpretasikan. Teknik sampling yang digunakan adalah purposive sampling. Hasil analisis menunjukkan bahwa partisipasi masyarakat Desa Jagara dalam pengembangan Waduk Darma hanya terlihat pada tahap pelaksanaan sebagai pelaku usaha dan pendukung kegiatan. Namun, pada tahap perencanaan dan pengawasan, partisipasi mereka masih minim bahkan tidak terlibat.